PENGEMBANGAN MEDIA DIGITAL STORYTELLING BERBASIS KEARIFAN LOKAL KOTA MALANG KELAS IV PADA MATERI CERITA TENTANG DAERAHKU - Naila Nisa' Uttohiriah; Anwar, Moh. Farid Nurul; Chotimah, Chusnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a digital storytelling medium based on the local wisdom of Malang City on the subject of Stories about My Region for fourth-grade elementary school students that is valid and effective for use in learning. This study was motivated by the low level of interest and engagement among students because learning is still dominated by lecture methods and textbooks. The research used the Research and Development (R&D) method with a modified Borg and Gall model, through the stages of potential and problems, data collection, product design, design validation, product revision, small group trials, further revision, large group trials, and valid and effective products. The research subjects were 14 students and fourth-grade teachers at SDN Merjosari 3 Malang City. Data were obtained through expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The results showed that the media obtained a highly valid category from subject matter experts (95.45%), language experts (93.75%), media experts (95.31%), and student and teacher response questionnaires (95%). The pilot test results also showed that the media was effective in increasing student interest and learning outcomes, with average scores in the aspects of attitude (93.42), skills (87.77), and knowledge (93.88). Thus, the digital storytelling media based on the local wisdom of Malang City is valid and effective for use as learning media in elementary schools.